The Correlation Between Years of Employment and Daily Noise Exposure Duration on Noise Induced Hearing Loss (NIHL) among Employees of the River Lake and Ferry Transportation (ASDP) at the ENT Clinic of the NTB Provincial Hospital - Rahman, Moch. Aulia; Widiastuti, Ida Ayu Eka; Wardoyo, E. Hagni (Jurnal Biologi Tropis, 2025)
Smoking NIHL (Noise-induced hearing loss) is a condition of hearing loss, namely sensorineural deafness due to long-term exposure to noise. This disease generally causes bilateral, irreversible, and progressive deafness. The purpose of this study was to see if there was a significant relationship between length of work and duration of daily noise exposure with the incidence of NIHL in ASDP employees. The research method was Cross-sectional and the data obtained were primary data and secondary data taken using the non-probability consecutive sampling technique. The materials or instruments used in the data collection process were questionnaires for primary data and medical records for secondary data. The data analysis process was carried out using an analytical test using Fisher-exact with relevant results p-value <0.05. After the analytical test was carried out, there was no significant relationship between length of work and the incidence of NIHL in ASDP employees at the ENT Polyclinic of the NTB Provincial Hospital (p = 0.34), and there was also no significant relationship between the duration of daily noise exposure and the incidence of NIHL in ASDP employees at the ENT Polyclinic of the NTB Provincial Hospital (p = 0.40). The conclusion of this study is that there is no significant relationship between length of work and duration of daily noise exposure with the incidence of NIHL in ASDP employees at the ENT Polyclinic of the NTB Provincial Hospital.